Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41586-020-2105-3
|View full text |Cite
|
Sign up to set email alerts
|

U1 snRNP regulates chromatin retention of noncoding RNAs

Abstract: Thousands of noncoding transcripts exist in mammalian genomes, and they preferentially localize to chromatin. Here, to identify cis-regulatory elements that control RNA-chromatin association, we developed a high-throughput method named RNA element for subcellular localization by sequencing (REL-seq). Coupling REL-seq with random mutagenesis (mutREL-seq), we discovered a key 7-nt U1 recognition motif in chromatin-enriched RNA elements. Reporter assays indicated a direct role for U1 snRNP recognition in regulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 121 publications
8
148
0
1
Order By: Relevance
“…Bazin et al 2017 ; Hsu et al 2016 ), and some of these lncRNAs could eventually contribute to biogenesis of small peptides. A set of nuclear lncRNAs are bound by chromatin, and this localization can be stabilized by U1 snRNP (U1 small nuclear ribonucleoprotein particle) in mammals (Yin et al 2020 ). Chromatin-associated lncRNAs potentially influence TF binding or the functionality of enhancers (Shlyueva et al 2014 ).…”
Section: Characteristics Of Lncrnasmentioning
confidence: 99%
“…Bazin et al 2017 ; Hsu et al 2016 ), and some of these lncRNAs could eventually contribute to biogenesis of small peptides. A set of nuclear lncRNAs are bound by chromatin, and this localization can be stabilized by U1 snRNP (U1 small nuclear ribonucleoprotein particle) in mammals (Yin et al 2020 ). Chromatin-associated lncRNAs potentially influence TF binding or the functionality of enhancers (Shlyueva et al 2014 ).…”
Section: Characteristics Of Lncrnasmentioning
confidence: 99%
“…U1 RPPs also included previously reported U1 interactor RNA polymerase II (Spiluttini et al, 2010; Yu and Reed, 2015) (Figure 3F), which is required for a noncanonical role of U1 in chromatin retention of ncRNAs (Yin et al, 2020). Moreover, U1 RPL retrieved proteins involved in chromatin remodeling, DNA modification, histone modification, and transcription (Table S1), which could be regulated by chromatin-associated ncRNAs (Huang et al, 2020; Li and Fu, 2019).…”
Section: Introductionmentioning
confidence: 58%
“…Therefore, affinity interactions to chromatin-binding proteins cannot fully account for the specific localization of lncRNAs to precise loci. Another explanation was recently proposed: a study reported that the U1 snRNP interacts with transcriptionally engaged POL II to tether and mobilize lncRNAs to chromatin in a transcription-dependent manner [ 53 ]. In this study, we demonstrated that lnc-eRNAs bound histone H4, which seemed to control the chromatin retention and cis regulation function of lnc-eRNAs.…”
Section: Discussionmentioning
confidence: 99%